PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Soebijantoro Soebijantoro (Universitas PGRI Madiun, 2011)
Character education relates to all of ability of any individual to interact with the environment, which copes with moral, attitude and behavior. One’s character is supposed to be good if he / she has moral knowledge, sense and action. Substantially, moral education is carried out affectively which deals with mentality, courage and hope, image and belief. Best belief of something is the result of learning process, coping with rational internalization about truths and well-being. Social Science is hoped to serve the moral education content, since it facilitates students with ability to adapt to the environment, to build knowledge, and to nurture the culture. All of those performances can be developed by the aplication of varied approaches of Social science.